Improved science learning outcomes of animal life cycle materials using audio-visual media in grade V - Fitriani Fitriani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve the learning outcomes of class V students in science subject matter animal life cycle material. This research is a Classroom Action Research which is conducted in two cycles with the stages of each cycle being planning, implementing action, observing and reflecting. The subjects of this study were students of class VA SD Negeri 2 Tambakmulyo for the 2020-2021 school year. There were 24 students. Data collection techniques using observation and tests. The conclusion of this study is that the use of audio-visual media can improve science learning outcomes in grade V SD Negeri 2 Tambakmulyo for the 2020/2021 academic year. This is evidenced by the percentage of learning completeness in the first cycle of 62.5% and in the second cycle it increased to 91.27%. The class average in the first cycle was 74.58 and the second cycle increased to 77.91.